Physiological and environmental effects on calving intervals in milking crossbred cows of the production system at the CNPGL/Embrapa - Filho, Geraldo Noronha Junqueira; Verneque, Rui da Silva; Lemos, Álvaro de Matos; da Silva, Hamilton Carmélio Machado; Reis, Ronaldo Braga (Pesquisa Agropecuaria Brasileira, 1992)
This study was conducted with the data from 131 crossbred Holstein-Ze-bu-Gir (H-Z) cows in the Production System which was introduced in 1977 at the National Center of Research of Dairy Cattle (CNPGL/EMBRAPA), Coronel Pacheco, MG, Brazil. All informations were collected from individual zootechnical files, from 1977 to 1987. The effects of physiological and environmental factors on the calving intervals were studied. Cal-ving intervals averaged 406 ± 8 days (13.3 ± 0.3 months). For this variable the following factors showed significant effects: year of parturition, genetic groups (1/2 blood breed sho-wed longer intervals), calving order (decreasing intervals from first to third parity).